Synthesis and characterization of a polyester based on citric acid/ethylene glycol/glycerol. Issue 12 (2nd December 2021) - Olarte-Paredes, A.; Salgado-Delgado, A. M.; García-Fuentes, J.J.; Salgado-Delgado, R.; Cedillo-Valverde, G.; López-Lara, T.; Hernández-Zaragoza, J.B.; Castaño, V. M.
Abstract: The synthesis and characterization of a novel polyester, based on citric acid and two plasticizers (glycerol -GLY- and ethylene glycol -EG-) using concentration CA:Plasticizer ratios (1:1, 1:2 and 1:3), is described. Fourier Transform Infrared Spectroscopy (FTIR) and Nuclear magnetic resonance (C-NMR) confirmed the functional groups characteristic of polyester, such as O-H, C-H, C-O, and C = O. Scanning Electron Microscopy (SEM) showed the morphology changes when mixed with the plasticizers. Thermogravimetric analysis (TGA) showed that the degradation began at 525 °C for polyester with ethylene glycol, and at 575 °C for polyester with glycerol. The contact angle measurements showed that the polyester obtained is hydrophilic. The use of EG or GLY yielded similar contact angle results (average of 65°). Differential scanning calorimetry (DSC) showed that the crystalline structure of citric acid disappeared due to the polymerization and the effect of plasticizers on the polymer network. The original contribution of this work consists in the use of ethylene glycol as a plasticizer, not reported in the literature, demonstrating the formation of the polyester with better mechanical properties when using ethylene glycol as compared to glycerol. Graphical Abstract: UF0001